Autism, social connectedness, and minimal social acts. (February 2019) - León, Felipe
Autism spectrum condition (henceforth ASC) is a complex psychopathological condition characterized by repetitive and restricted patterns of behaviors, as well as by impairments in social interaction and communication. This article focuses on the idea that ASC involves impairments in the capacity to connect with the feelings and actions of others. The metaphor of social connectedness might be considered somewhat uninformative, hardly specific of ASC, and ultimately compatible with a variety of competing approaches to social impairments in ASC. Nevertheless, here I develop an account of social connectedness which plays a distinctive and informative role in further understanding ASC. My strategy is to explore the role of social reciprocity in relation to the difficulties that persons with ASC have with social connectedness. Drawing on the work of Peter Hobson, I propose that such difficulties primarily involve experiences and actions that require the uptake or response from another subject for their fulfillment. I clarify and develop this idea by introducing the concept of minimal social act, inspired by the work of the phenomenologists Adolf Reinach and Dietrich von Hildebrand, and by discussing some 4E (i.e., embodied, enactive, embedded, and extended) approaches to ASC. On the current proposal, minimal social acts are pervasive and developmentally critical experiences that have built into their conditions of success a receptiveness or responsiveness from the subject to whom they are directed.